2021
DOI: 10.1186/s12877-021-02253-3
|View full text |Cite
|
Sign up to set email alerts
|

The preventive efficacy of vitamin B supplements on the cognitive decline of elderly adults: a systematic review and meta-analysis

Abstract: Background The irreversibility of cognitive impairment of Alzheimer’s disease (AD) prompts that preventing or delaying the onset of AD should be a public health priority. Vitamin B supplements can lower the serum homocysteine (Hcy) level, but whether it can prevent cognitive decline or not remains unclear. We aimed to evaluate the preventive efficacy of vitamin B supplements on the cognitive decline of elderly adults. Methods We searched PubMed, Em… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 52 publications
1
22
0
1
Order By: Relevance
“…The accelerated cognitive aging associated with food insecurity can lead to poor mental health which can result in acquiring functioning disability at the later ages. The studies based on micronutrient deficiency also found cognitive impairment among those who have deficiency of Vitamin B [ 26 , 27 ]. Also, the findings of our study corroborates with the findings from the latest systematic review done by Iolascon et al, 2017, where they found that availability of 16 major micronutrients in the diets can reduce the risk of cognitive impairment among elderly in world [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accelerated cognitive aging associated with food insecurity can lead to poor mental health which can result in acquiring functioning disability at the later ages. The studies based on micronutrient deficiency also found cognitive impairment among those who have deficiency of Vitamin B [ 26 , 27 ]. Also, the findings of our study corroborates with the findings from the latest systematic review done by Iolascon et al, 2017, where they found that availability of 16 major micronutrients in the diets can reduce the risk of cognitive impairment among elderly in world [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate nutrition caused by FI has also shown an association with unfavourable health outcomes such as obesity, anxiety, depression, and suicide, which activates the hypothalamic-pituitary-adrenal axis and triggers the secretion of glucocorticoids in the adrenal glands [ 24 , 25 ]. The deficiency of several vitamins and micronutrients also leads to various cognitive impairment which often leads to chronic health state, like Alzheimer’s [ 23 , 26 – 28 ]. So it is important to study the relevance of food insecurity in context of elderly which leads to cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Elevations in GSH via NAC and glutamylcysteine ethyl ester (GCEE) administration may improve neuroprotection in the brain, thereby improving cognitive impairments and possibly preventing the progression of MCI to Alzheimer's disease (Pocernich and Butterfield, 2012). Vitamin B supplements including folate appear to be effective in the prevention of cognitive decline in elderly people (Li et al, 2021). Moreover, folate administration may lower homocysteine levels and O&NS (Zhou and Chen, 2019) and folate administration, as well as the combination of folate with other nutrients, may be beneficial in the treatment of MCI and Alzheimer's disease (Puga et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This effect is lacking in parameters of information processing speed, episodic memory, and executive function. Based on this, the authors recommend vitamin B supplements to be considered as a preventive medication to MCI patients since vitamin B might delay or maintain the cognitive decline of elderly adults [ 167 ]. In line with this evidence of the beneficial effects of vitamin B12 in individuals without or with mild cognitive impairments, a recent randomized controlled trail reported that the combination of oral vitamin B12 (25 µg) and folic acid (800 µg) for six months reduced the levels of peripheral inflammatory cytokines and improved cognitive performance significantly in MCI patients, assessed by the measurement of the full-scale intelligence quotient (IQ), verbal IQ as well as information and digit span scores.…”
Section: Clinical Studiesmentioning
confidence: 99%